Characterization of CD4 T Cell Epitopes of Infliximab and Rituximab Identified from Healthy Donors - Hamze, Moustafa; Meunier, Sylvain; Karle, Anette; Gdoura, Abdelaziz; Goudet, Amélie; Szely, Natacha; Pallardy, Marc; Carbonnel, Franck; Spindeldreher, Sebastian; Mariette, Xavier; Miceli-Richard, Corinne; Maillère, Bernard (Frontiers in Immunology, 2017)
The chimeric antibodies anti-CD20 rituximab (Rtx) and anti-TNF infliximab (Ifx) induce anti-drug antibodies (ADAs) in many patients with inflammatory diseases. Because of the key role of CD4 T lymphocytes in the initiation of antibody responses, we localized the CD4 T cell epitopes of Rtx and Ifx. With the perspective to anticipate immunogenicity of therapeutic antibodies, identification of the CD4 T cell epitopes was performed using cells collected in healthy donors. Nine T cell epitopes were identified in the variable chains of both antibodies by deriving CD4 T cell lines raised against either Rtx or Ifx. The T cell epitopes often exhibited a good affinity for HLA-DR molecules and were part of the peptides identified by MHC-Associated Peptide Proteomics (MAPPs) assay from HLA-DR molecules of dendritic cells loaded with the antibodies. Two third of the T cell epitopes identified from the healthy donors stimulated PBMCs from patients having developed ADAs against Rtx or Ifx and promoted the secretion of a diversity of cytokines. These data emphasize the predictive value of evaluating the T cell repertoire of healthy donors and the composition of peptides bound to HLA-DR of DCs to anticipate and prevent immunogenicity of therapeutic antibodies.